2023
DOI: 10.1108/srj-06-2023-0332
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking sustainable success: exploring the impact of transformational leadership, organizational culture, and CSR performance on financial performance in the Italian manufacturing sector

Muhammad Junaid Ahsan

Abstract: Purpose This study aims to investigate how organizational culture (OC) and transformational leadership (TL) affect corporate social responsibility (CSR) performance (environmental performance and social performance) and financial performance (FP) in the context of the Italian manufacturing sector. Grounded in resource-based view theory, this study explores how these factors influence sustainable firm performance. Design/methodology/approach Data gathered from 260 employees were analyzed to examine the multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Hofstede et al (1991) found that organizational culture is not only a single entity but can also be divided into different components, such as individual and collective, and power distance, which may affect CSR activities differently. A study by Ahsan (2024) has introduced a Competing Values Framework that divides organizational culture into four types: race, hierarchy, market, hierarchy, and race-branded culture, which is transformational and management, CSR rather than market culture perspective but more aligned with practices, which prioritize efficiency and consistency (Abdelwahed & Soomro, 2024). In the construction industry, the role of organizational culture is critical because of the impact of the enterprise on the environment and the local community.…”
Section: Organizational Culture and Csrmentioning
confidence: 99%
“…Hofstede et al (1991) found that organizational culture is not only a single entity but can also be divided into different components, such as individual and collective, and power distance, which may affect CSR activities differently. A study by Ahsan (2024) has introduced a Competing Values Framework that divides organizational culture into four types: race, hierarchy, market, hierarchy, and race-branded culture, which is transformational and management, CSR rather than market culture perspective but more aligned with practices, which prioritize efficiency and consistency (Abdelwahed & Soomro, 2024). In the construction industry, the role of organizational culture is critical because of the impact of the enterprise on the environment and the local community.…”
Section: Organizational Culture and Csrmentioning
confidence: 99%
“…Transformational leaders not only focus on achieving current goals, but also have a vision that involves nurturing the next generation who can inherit the legacy of innovation and leadership. By creating and nurturing an environment that supports talent development, transformational leadership makes a long-term contribution to the sustainability of innovation in the organisation [22]. In addition to supporting direct innovation through the development of new ideas, transformational leaders are committed to unearthing untapped leadership potential, creating development programmes, and providing mentorship to ensure that the organisation has a cadre of leaders who are diverse, creative, and ready to face future challenges [23].…”
Section: Journal Of Contemporary Administration and Management (Adman)mentioning
confidence: 99%
“…Unfortunately, there has been little research in this domain, which highlights a gap for future research. Added to this, most CSR research have concentrated on developed nations (Ahsan, 2023; Davidson, 2016), leaving questions and concerns related to the applicability and transferability of established CSR frameworks in developing countries (Jamali & Karam, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study complements this stream of research by investigating how employee commitment and corporate reputation can influence the connection between CSR and CCA. Second, while the majority of CSR and environment-related research were conducted in Western and developed countries (Ahsan, 2023; S. Ali et al, 2022; Davidson, 2016; Xu et al, 2022), we have studied CSR in the Vietnamese context.…”
Section: Introductionmentioning
confidence: 99%